Two new genera of fossil palaeontinids from the Middle Jurassic in Daohugou, Inner Mongolia, China (Hemiptera, Palaeontinidae) - Wang, Ying; Ren, Dong (Zootaxa, 2007)
In this paper two new genera and three new species of Palaeontinidae are described: Quadraticossus gen.nov., containing two new species, Q. fangi and Q. longicaulis; Hamicossus laevis gen. et sp. nov. These two new genera are established based on both complete forewings and hind wings. All of them were collected from the Middle Jurassic Jiulongshan Formation at Daohugou Village, Inner Mongolia. The type specimens are deposited in the College of Life Science, Capital Normal University.